Effect of sulphur supplementation fed wheat straw based diets on performanance of sheep* - SAINI, N; SHARMA, T; ARYA, R S (The Indian Journal of Animal Sciences, 2011)
Optimum level of sulphur required for local fodder of sheep was determined by in vitro studies and further evaluated in 20 male Marwari sheep in completely randomised design. Control group (T1) was fed wheat straw (Triticum aesativa), and concentrate mixture containing 10% CP whereas, group T2 was offered wheat straw supplemented with sulphur @ 0.18% DM basis, and in group T3, T4 and Ts wheat straw of T2 was replaced with 50% groundnut straw (Arachis hypogaea), lnoth straw (Phaseolus aconitifolius), and sewan hay (Lasirus sindicus), respectively. Intake,% digestibilityÂ· and plane of nutritient utilization were significantly influenced by' supplementation of sulphur and type of roughage. Supplementation of sulphur significantly improved clean wool yield, staple length and medullation percentage as well as total live weight gain in supplemented groups compared to control group. The study indicated that supplementation of sulphur needed for straw diet to maximize utilization of nutrients and moth straw added sulphur supplemented wheat straw diet was superior among all the experimental diets.Â